Kurikulum Pendidikan Budaya pada Satuan Pendidikan Rintisan - Sutjipto -- (Jurnal Pendidikan dan Kebudayaan, 2013)
This study aims to obtain a picture related to the implementation of the cultural curriculum development efforts 300 units on preschool education, primary education, secondary education, exceptional education, and educational equality that has been developed as a pilot model in 2012. The technique used in this study include descriptive study. A descriptive study with critical discourse analysis, in the sense of collecting facts and study the situation, outlook, and ongoing process. The main information collected through secondary data such as documentation reports, the results of focus group discussions, and participant observation. Data processed by the implementation of activities, and the results of the model unit activity throughout the pilot study culture curriculum implementation. Data analysis techniques used description, and interpretation. Results showed that: 1) the growth of a culture growing in a positive direction; 2) norms and values are implemented affects not only the daily activities, but also to motivate and encourage; 3) norms and values not only serves as a means of interadhesive one another, but also beneficial for the improvement of social skills; 4) norms and values as the foundation footing to build a more advanced civilization and humane for the future seemed to be entrenched; and 5) the willingness of stakeholders spool still be a problem in the implementation.